2012
DOI: 10.3842/sigma.2012.099
|View full text |Cite
|
Sign up to set email alerts
|

On the Number of Real Roots of the Yablonskii-Vorob'ev Polynomials

Abstract: Abstract. We study the real roots of the Yablonskii-Vorob'ev polynomials, which are special polynomials used to represent rational solutions of the second Painlevé equation. It has been conjectured that the number of real roots of the nth Yablonskii-Vorob'ev polynomial equals n+1 2. We prove this conjecture using an interlacing property between the roots of the Yablonskii-Vorob'ev polynomials. Furthermore we determine precisely the number of negative and the number of positive real roots of the nth Yablonskii-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…We notice that the same question for Painlevé II rationals has recently been settled by many authors with a wealth of different methods[2,5,6,41,52,53].…”
mentioning
confidence: 77%
“…We notice that the same question for Painlevé II rationals has recently been settled by many authors with a wealth of different methods[2,5,6,41,52,53].…”
mentioning
confidence: 77%
“…It has been shown that the polynomials tQ n pzqu 8 n"0 all have simple roots and that Q m and Q m´1 can have no roots in common [20], facts that are consistent via (1.8) with the fact that all poles of ppyq are simple with residues ˘1. Real roots of the Yablonskii-Vorob'ev polynomials correspond to real poles of ppyq, and these have been studied extensively by Roffelsen who has shown that all nonzero real roots are all irrational [34] and that there are precisely tpn `1q{3u negative roots of Q n and tpn `1q{2u total real roots of Q n , and Q n p0q " 0 if and only if n " 1 pmod 3q [35]. Also, the real roots of Q n`1 and Q n´1 interlace, as was proven by Clarkson [10].…”
Section: Representation In Terms Of Special Polynomialsmentioning
confidence: 99%
“…Generalizing further to y ∈ C, the idea that the rational Painlevé functions considered here may have a particularly interesting structure in the complex y-plane when m is large is indicated by two previous results. Numerically generated plots [9,17,19,24,30] of the m(m + 1)/2 complex zeros of the related mth Yablonskii-Vorob'ev polynomial (see [34,35]) form a highly regular pattern in a triangular-type region with curved sides of size proportional to m 2/3 as m → ∞ (see also the work of Roffelsen [32,33] for other recent results on the Yablonskii-Vorob'ev polynomials, including interlacing properties of the real roots). The rational Painlevé-II functions P m are the logarithmic derivatives of ratios of successive Yablonskii-Vorob'ev The zeros (open circles) and poles (filled circles) of U 13 (y) (left) and P 13 (y) (right) in the complex x-plane, where x = (13 − 1 2 ) −2/3 y, along with the m-independent boundary of the region T .…”
Section: Solutions Of the Inhomogeneousmentioning
confidence: 99%
“…Generalizing further to y ∈ C, the idea that the rational Painlevé functions considered here may have a particularly interesting structure in the complex y-plane when m is large is indicated by two previous results. Clarkson and Mansfield [8] noted from numerically-generated plots that the m(m + 1)/2 complex zeros of the related m th Yablonskii-Vorob'ev polynomial form a highly regular pattern in a triangular-type region with curved sides of size proportional to m 2/3 as m → ∞ (see also the work of Roffelson [25,26] for other recent results on the Yablonskii-Vorob'ev polynomials, including interlacing properties of the roots). The rational Painlevé-II functions P m (y) are the logarithmic derivatives of ratios of successive Yablonskii-Vorob'ev polynomials (or equivalently, the Painlevé-II functions U m (y) are themselves such ratios), and thus the zeros and poles of U m and P m exhibit the same qualitative behavior (see Figure 1, in which we present figures similar to those in [8] but in a rescaled independent variable).…”
mentioning
confidence: 99%